(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
In this article, the history of the origin of the image of a hermit in mystical literature,Sufism and asceticism, the peculiarities of ascetics,the writers who studied asceticism andtheir views on the term, their views on impurity and honesty, were analyzed on the basis of Alisher Navoi’s poems about ascetics.